2001
DOI: 10.1177/107319110100800403
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Depression in Russian Psychiatric Patients: Validity of MMPI and Rorschach

Abstract: We tested the criterion, concurrent, and content validity of depression indicators in 180 Russian psychiatric patients. Indicators from the Exner Rorschach (DEPI, CDI) and the Russian MMPI (Berezin Scale 2, Wiggins depression content) were compared to Hamilton (HRSD) scores and 3 types of diagnosis: traditional Russian, contemporary Western (ICD-10), and a mixed version. The MMPI scales had significant associations with each other and each criterion. The Rorschach indexes were unrelated to all other variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This is the same sample used in a previous article (Ritsher et al, 2001) focusing on indicators of depression. Of these 180 participants, 108 were inpatients at the Russian Academy of Medical Sciences, Research Center for Mental Health (RCMH).…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the same sample used in a previous article (Ritsher et al, 2001) focusing on indicators of depression. Of these 180 participants, 108 were inpatients at the Russian Academy of Medical Sciences, Research Center for Mental Health (RCMH).…”
Section: Methods Participantsmentioning
confidence: 99%
“…For example, the threshold for clinical significance was substantially raised for Scales 2 and 4, and the subject of the items was changed from "I" to "you." In terms of content, Berezin et al's (1994) version is more similar to the MMPI-2 than to the original MMPI because most of the same changes made to the MMPI to create the MMPI-2 were also made to the MMPI to create the Berezin et al's (1994) version of the MMPI (for further details, see Ritsher, 1998). For example, many items in the original MMPI that pertain to bowel function and religion are absent from both the MMPI-2 and Berezin et al's (1994) MMPI.…”
Section: Notementioning
confidence: 99%
See 2 more Smart Citations
“…This is true for both adults and adolescents. For example, six of eight studies conducted independently of the Rorschach Workshops found no significant relation between the revised DEPI and psychiatric diagnoses (Archer & Krishnamurthy, 1997;Ball, Archer, Gordon, & French, 1991;Caine, Frueh, & Kinder, 1995;Meyer, 1993;Ritsher, Slivko-Kolchik, & Oleichik, 2001;Sells, 1990Sells, / 1991; see also Meyer, 2001a), one study yielded mixed results (Ilonen et al, 1999), and only one study yielded unmixed positive results (Jansak, 1996(Jansak, /1997.…”
Section: Research On the Assessment Of Psychopathologymentioning
confidence: 99%